Pengaruh Insentif Pajak Kendaraan Bermotor Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Selama Masa Pandemi Covid 19 - Novianti Syarif; Amin Dara; Dwi Yana Amalia Sari Fala (AKUNTANSI 45, 2023)
The purposes of this study are: (1) To analyze the effect of vehicle tax incentives on vehicle taxpayer compliance during the covid 19 pandemic and (2) To analyze the effect of service quality on vehicle taxpayer compliance during the covid 19 pandemic. The object of this study is a vehicle taxpayer registered at the Ternate City SAMSAT office. This type of research is quantitative research. The analytical model used in this study is multiple linear regression analysis using Smart PLS. Based on the results of the study, the results showed that (1) Vehicle tax incentives had an effect on vehicle taxpayer compliance during the covid 19 pandemic and (2) Service Quality had an effect on vehicle taxpayer compliance during the covid 19 pandemic.